Toxic Leadership in Education: A Systematic Review - Birol Başkan (Har Press Indonesia, 2020)
There has been sparse research explicitly looking at toxic leadership, a more complex and comprehensive destructive leadership style in higher education settings, despite the breadth of literature on destructive leadership styles and their impact on organizational culture, mission, and individuals. With the introduction of the term “toxic leadership” in 1996, the corporate world and military agencies began to examine whether leadership could lead to a toxic culture. As of 2007, studies have been unable to connect the concept of learning in higher education systems to the phenomenon of